2018
DOI: 10.1111/1467-8551.12285
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Behavioural Component of the S&P 500 and its Relationship to Financial Stress and Aggregated Earnings Surprises

Abstract: Scholars in management and economics have shown increasing interest in isolating the behavioural dimension of market evolution. Indeed, by improving forecast accuracy and precision, this exercise would certainly help firms to anticipate economic fluctuations, thus leading to more profitable business and investment strategies. Yet, how to extract the behavioural component from real market data remains an open question. By using monthly data on the returns of the constituents of the S&P 500 index, we propose a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Similarly, management studies have also shown that behavioural biases and sentiment in organizations may affect managers' decision‐making processes (e.g. Caporin, Corazzini and Costola, 2019; Latham and Braun, 2010; Maule and Hodgkinson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, management studies have also shown that behavioural biases and sentiment in organizations may affect managers' decision‐making processes (e.g. Caporin, Corazzini and Costola, 2019; Latham and Braun, 2010; Maule and Hodgkinson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Influences that have to be identified and mitigated to avoid wrong decisions that can cause economic damage (Chang & Lin, 2015;Nofsinger, 2018). However, accepting the fact that financial decisions are prone to biases, researchers turned their view to the potential positive side: understanding the behavioral mechanics (Caporin et al, 2019;Pompian, 2012), could help to make better financial and investment business decisions (Pompian, 2011). Extensive academic literature has explored this angle suggesting how investors could take advantage of it (Pompian & Longo, 2004;Puaschunder, 2017).…”
Section: Investorsmentioning
confidence: 99%
“…Several studies provided empirical evidence of the relationship between market reactions and different types of news such as macroeconomic, environmental, corporate governance, and earning news (see, among others, Hamilton, 1995 , Zhang et al, 2013 , Huang, 2018 , Caporin et al, 2019 , Carlini et al, 2020 ). The ability to investigate the impact of news on stock prices has recently increased thanks to the use of natural language processing (NLP) in finance and economics ( Xing et al, 2018 , Wan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%